Videogestützte Autismustherapie: Implikation, Gestaltung und Wirksamkeit - Nashef, Anas (psychopraxis. neuropraxis, 2020)
Although alternative settings like video-supported therapies are nothing new, the outbreak of COVID-19 has led to an explosive increase in this type of therapy and it is expected that this “novel” format of the therapeutic community will at least retain its proportionate share. At present, autism therapy also holds an above-average number of therapy sessions using the video format. Apart from the challenges of this rethinking process and the need for all participants to adapt, the implications and chances of success of this format, which should be understood to be supplementary in the local context, are becoming manifest, not only in view of the newly gained experience. This article is aimed at introducing video-supported autism therapy, outlining possible therapeutic interventions, and discussing the state of research in terms of the efficacy of this form of therapy.